ANTIHYPERTENSIVE ACTIVITY OF QUINOA (Chenopodium quinoa Willd.) PROTEIN HYDROLYSATES - Moreno-Limón, Sergio; González-Luna, Rodrigo (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Nowadays, there has been an increase in the number of studies focused on the search for bioactive compounds produced by hydrolytic reactions from natural sources, such as the Quinoa grain, which represents an interesting agro-alimentary source that can have a beneficial influence on health, specifically antihypertensive potential. For this reason, the aim of the present study was to evaluate the antihypertensive activity of the protein hydrolysates obtained of Quinoa, which results important at the time to consider the incorporation of such peptides in the design of functional foods. Materials and Methods: Quinoa (Chenopodium quinoa Willd.) seeds were ground and the obtained flour was degreased and the protein isolate was obtained by isoelectric precipitation. The protein isolate was enzymatically hydrolyzed with Alcalase® and Flavourzyme® and the antihypertensive effect of peptides against angiotensin converting enzyme was evaluate using a mixture of 50 μL of sample, 50 μL of ACE working solution, 200 μL of substrate working solution and the fluorescence was determined with a microplate fluorometer following these characteristics: λ (excitation) = 355-375 nm; λ (emission) = 400-430 nm. Results: Peptides obtained using Alcalase® (protein content= 72.13%; DH= 31.22%) showed the highest inhibitory activity against the angiotensin converting enzyme (ACE), close to 88%. Conclusion: The Quinoa protein hydrolysates can be considered as a new agri-food source to be incorporated in the elaboration of functional foods with antihypertensive potential.